2013
DOI: 10.7314/apjcp.2013.14.11.6757
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MDR1 Increases the Sensitivity to Adriamycin in Drug Resistant Gastric Cancer Cells

Abstract: Gastric cancer is one of the most frequently occurring malignancies in the world. Development of multiple drug resistance (MDR) to chemotherapy is known as the major cause of treatment failure for gastric cancer. Multiple drug resistance 1/P-glycoprotein (MDR1/p-gp) contributes to drug resistance via ATP-dependent drug efflux pumps and is overexpressed in many solid tumors including gastric cancer. To investigate the role of MDR1 knockdown on drug resistance reversal, we knocked down MDR1 expression using shRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…Many studies suggested that polymorphism of multi-drug resistance 1 (MDR1) gene may modulate the incidence of cancer risk (Zhu et al, 2013;de Oliveira et al, 2014). MDR1 gene is a member of the ABC (ATPbinding cassette) family that encodes a membrane-bound phosphoglycoprotein (P-gp).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggested that polymorphism of multi-drug resistance 1 (MDR1) gene may modulate the incidence of cancer risk (Zhu et al, 2013;de Oliveira et al, 2014). MDR1 gene is a member of the ABC (ATPbinding cassette) family that encodes a membrane-bound phosphoglycoprotein (P-gp).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nrf2 has been emerged as a potent therapeutic target to overwhelming chemoresistance. Therefore, identification of potent and unique Nrf2 inhibitor for sensitizes a broad spectrum of cancer cells urgently needed (Zhu et al, 2013) Flavonoids act as a free radical scavenger, immune system modulator, and antioxidant agent. These characteristics with low toxicity, making them good option for cancer chemoperventive agent (Lopez-Lazaro, 2009;Xu et al, 2009;Akan and Garip, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have devoted themselves to exploring the pathogenesis of cancer and attempting to seek effective therapies against various cancers including gastric carcinoma. Multi-factors including abnormal expression, aberrant methylation and single nucleotide polymorphisms (SNPs) of genes that associated with cell proliferation, cell differentiation and other key cell processes have been identified to be related to tumorigenesis, in addition, small regulators such as microRNA also have been shown to play an important role in cancers (Guo et al, 2012;Jing et al, 2012;Chen et al, 2013;Gao et al, 2013;Yao et al, 2013;Zhu et al, 2013). Based on these advances of mechanisms, treatments against cancer are no longer confined to traditional chemotherapy.…”
Section: Discussionmentioning
confidence: 99%